Pedagogical Methods of Using a Didactic Approach in Creating Independent Study Tasks for Students of the Philological Education - Raupova, Laylo; Khursanov, Nurislom (MMIT Proceedings, 2024)
Organization of independent educational activities of students studying in the field of philological education requires skill and competence from the pedagogue. Independent education should be covered not only by library research, but also by a set of purposeful assignments developed by the pedagogue. In this article, recommended research on the integration of didactic approaches in the development and implementation of independent educational tasks for students of philological education is described. By examining current trends in philological education, reviewing didactic theories, and providing practical examples, this study aims to provide a comprehensive understanding of how didactic strategies can improve students' critical thinking, analytical skills, and autonomy in philological education.